Human hypocretin and melanin concentrating hormone levels are linked to emotion and social interaction - Blouin, Ashley M. (2013)
The neurochemical changes underlying human emotions and social behavior are largely unknown. Here we report on the changes in the levels of two hypothalamic neuropeptides, hypocretin-1 (Hcrt-1) and melanin concentrating hormone (MCH), measured in the human amygdala. We show that Hcrt-1 levels are maximal during positive emotion, social interaction, and anger, behaviors that induce cataplexy in human narcoleptics. In contrast, MCH levels are minimal during social interaction, but are increased after eating. Both peptides are at minimal levels during periods of postoperative pain despite high levels of arousal. MCH levels increase at sleep onset, consistent with a role in sleep induction, whereas Hcrt-1 levels increase at wake onset, consistent with a role in wake induction. Levels of these two peptides in humans are not simply linked to arousal, but rather to specific emotions and state transitions. Other arousal systems may be similarly emotionally specialized.